Role of PI3K in the Progression and Regression of Atherosclerosis - Zhao, Yunyun; Qian, Yongjiang; Sun, Zhen; Shen, Xinyi; Cai, Yaoyao; Li, Lihua; Wang, Zhongqun (Frontiers in Pharmacology, 2021)
Phosphatidylinositol 3 kinase (PI3K) is a key molecule in the initiation of signal transduction pathways after the binding of extracellular signals to cell surface receptors. An intracellular kinase， PI3K activates multiple intracellular signaling pathways that affect cell growth, proliferation, migration, secretion, differentiation, transcription and translation. Dysregulation of PI3K activity, and as aberrant PI3K signaling, lead to a broad range of human diseases, such as cancer, immune disorders, diabetes, and cardiovascular diseases. A growing number of studies have shown that PI3K and its signaling pathways play key roles in the pathophysiological process of atherosclerosis. Furthermore, drugs targeting PI3K and its related signaling pathways are promising treatments for atherosclerosis. Therefore, we have reviewed how PI3K, an important regulatory factor, mediates the development of atherosclerosis and how targeting PI3K can be used to prevent and treat atherosclerosis.